2016
DOI: 10.1016/j.joca.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Management options for femoroacetabular impingement: a systematic review of symptom and structural outcomes

Abstract: Although evidence supports improvement in symptoms after surgery in FAI, no studies have compared surgical and non-surgical treatment. Therefore no conclusion regarding the relative efficacy of one approach over the other can be made. Surgery improves alpha angle but whether this alters the risk of development or progression of hip OA is unknown. This review highlights the lack of evidence for use of surgery in FAI. Given that hip geometry may be modified by non-surgical factors, clarifying the role of non-sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 46 publications
1
42
0
1
Order By: Relevance
“…The most recent systematic review (29 clinical studies, 1911 patients) found a statistically significant improvement across all PROMs following hip arthroscopy for FAIS,18 echoing the conclusions of previous systematic reviews 1617181920. Of those patients, 1.7% experienced complications.…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 53%
See 1 more Smart Citation
“…The most recent systematic review (29 clinical studies, 1911 patients) found a statistically significant improvement across all PROMs following hip arthroscopy for FAIS,18 echoing the conclusions of previous systematic reviews 1617181920. Of those patients, 1.7% experienced complications.…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 53%
“…All these systematic reviews relied on mostly low quality evidence from case series and cohort studies 1617181920. A Cochrane Review from 2014 confirmed that no randomised controlled trials comparing arthroscopic hip surgery with conservative management had been published 21…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 99%
“…While there is some evidence that hip arthroscopy results in short to medium term symptomatic improvement in FAI, 6 8 these conclusions are based on examining patients only treated surgically, and no study has compared surgical with non‐surgical therapy. Although one systematic review concluded that symptom outcomes with hip arthroscopy were superior to non‐surgical management of FAI, 7 this conclusion may be misleading since the systematic review was largely based on case series with no head‐to‐head comparisons between surgical and non‐surgical groups.…”
Section: Evidence For Symptom Benefit Of Hip Arthroscopy For Pain In mentioning
confidence: 99%
“…Although surgical correction of hip bone shape provides a biologically plausible approach for reducing hip pain and slowing the incidence and progression of hip OA, the evidence supporting the use of hip arthroscopy in the management of FAI is limited 6 …”
mentioning
confidence: 99%
“…FAI is recognized as a common cause of non-arthritic hip pain and is defined as a motion-related clinical disorder of the proximal femur and acetabulum that may result in pain and decreased function [6,7]. This impingement is caused by abnormal morphology of the femoral head/neck junction (cam impingement), acetabular rim (pincer impingement) or both [8].…”
mentioning
confidence: 99%